2011
DOI: 10.3390/ijerph8051671
|View full text |Cite
|
Sign up to set email alerts
|

How Do Price Minimizing Behaviors Impact Smoking Cessation? Findings from the International Tobacco Control (ITC) Four Country Survey

Abstract: This paper examines how price minimizing behaviors impact efforts to stop smoking. Data on 4,988 participants from the International Tobacco Control Policy Evaluation (ITC) Four-Country Survey who were smokers at baseline (wave 5) and interviewed at a 1 year follow-up were used. We examined whether price minimizing behaviors at baseline predicted: (1) cessation, (2) quit attempts, and (3) successful quit attempts at one year follow up using multivariate logistic regression modeling. A subset analysis included … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
60
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(65 citation statements)
references
References 25 publications
4
60
1
Order By: Relevance
“…Similarly, individuals of low socioeconomic status (both low education attainment and low income) appear more likely to practice some uncontrolled price minimization strategies, which may include purchasing discount or deep discount cigarettes. This finding helps to rectify a discrepancy in the literature regarding if low socioeconomic status individuals practice cigarette price minimization strategies less frequently (Pesko et al, 2012) or more frequently than high socioeconomic status individuals (Choi et al, 2012;Licht et al, 2011). Including usage of discounted cigarettes is important in future research that analyzes the use of cigarette price minimization strategies by age or socioeconomic status.…”
Section: Discussionmentioning
confidence: 92%
See 3 more Smart Citations
“…Similarly, individuals of low socioeconomic status (both low education attainment and low income) appear more likely to practice some uncontrolled price minimization strategies, which may include purchasing discount or deep discount cigarettes. This finding helps to rectify a discrepancy in the literature regarding if low socioeconomic status individuals practice cigarette price minimization strategies less frequently (Pesko et al, 2012) or more frequently than high socioeconomic status individuals (Choi et al, 2012;Licht et al, 2011). Including usage of discounted cigarettes is important in future research that analyzes the use of cigarette price minimization strategies by age or socioeconomic status.…”
Section: Discussionmentioning
confidence: 92%
“…This decrease may be a result of some potential smokers choosing not to smoke and more successful quit attempts among current smokers (Chaloupka et al, 2002;Chaloupka & Warner, 1999;Frieden et al, 2005;Hyland et al, 2005Hyland et al, , 2006Levy et al, 2000;Lewitt & Coate, 1982;Licht et al, 2011;McGoldrick & Boonn, 2010). Unfortunately, not all smokers will respond beneficially to tax increases, and some will continue their usual smoking behaviors by either using compensatory price minimization strategies (Choi, Hennrikus, Forster, & St Claire, 2012;DeCicca, Kenkel, & Liu, 2010;Fong et al, 2006;Frieden et al, 2005;Goolsble, Lovenheim, & Slemrod, 2010;Hyland, Higbee, Bauer, Giovino, & Cummings, 2004;Hyland et al, 2005Hyland et al, , 2006Licht et al, 2011;Pesko, Kruger, & Hyland, 2012; U.S. Department of Health and Human Services, 2000;White, Gilpin, White, & Pierce, 2005) or paying higher prices. Use of price minimization strategies, thus, mitigates the positive public health impact of cigarette price increases.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…28 A study conducted in 2 US counties located near American Indian reservations found that smokers who bought cigarettes on reserve were half as likely to attempt to quit, with a trend toward decreased cessation. 26 Previous literature using data from the International Tobacco Control study found that people purchasing low-tax or untaxed cigarettes were about 30% less likely to report attempting to quit, with no effect found on cessation.…”
mentioning
confidence: 99%